Salman Rushdie's luka and the fire of life (2010) - Mohd Ramli, Aimillia; Nuurzahirah, Ali (Universiti Putra Malaysia Press, 2018)
This study aims to identify the ways in which elements of magic realism in Salman Rushdie’s Luka and the Fire of Life (2010) are used to subvert notions of reality that are reflected through various mediums, from literary realism through non-literary discourses and, finally, time itself which is often regarded as objective. This paper seeks to show through its application of Hegerfeldt’s (2005) five prototypical features of magic realism that, firstly, words could be used to both represent fantasy as reality through the appropriation of realistic forms of writing to describe fantastical characters and events. Secondly, the use of an “ex- centric” or marginalised focaliser in the novel also enables it to challenge mainstream ideas regarding reality, specifically the conventional notion of Time. Time, as the novel implies, can be subjective as it is affected by the consciousness of the novel’s marginalised characters. Thirdly, words could also be used to subvert non-literary discourses. Fourthly, Time is also supernaturalised or personified in the narrative even though it neither has a physical nor an abstract form. Discussion on the opposition between fatalism and free will appears in this context of time as determining the destiny of the novel’s characters who appears to challenge it through their free will. Finally, a subverted reality is represented through literalisation which is when figurative expressions manifest themselves literally, thus crossing the boundaries between words and reality.